"Atypical" Pleomorphic Lipomatous Tumor: A Clinicopathologic, Immunohistochemical and Molecular Study of 21 Cases, Emphasizing its Relationship to Atypical Spindle Cell Lipomatous Tumor and Suggesting a Morphologic Spectrum (Atypical Spindle Cell/Pleomorphic Lipomatous Tumor). (November 2017) - Creytens, David; Mentzel, Thomas; Ferdinande, Liesbeth; Lecoutere, Evelyne; van Gorp, Joost; Atanesyan, Lilit; de Groot, Karel; Savola, Suvi; Van Roy, Nadine; Van Dorpe, Jo; Flucke, Uta
Abstract : The classification of the until recently poorly explored group of atypical adipocytic neoplasms with spindle cell features, for which recently the term atypical spindle cell lipomatous tumor (ASLT) has been proposed, remains challenging. Recent studies have proposed ASLT as a unique entity with (in at least a significant subset of cases) a specific genetic background, namely deletions/losses of 13q14, including RB1 and its flanking genes RCBTB2, DLEU1, and ITM2B . Similar genetic aberrations have been reported in pleomorphic liposarcomas (PLSs). This prompted us to investigate a series of 21 low-grade adipocytic neoplasms with a pleomorphic lipoma–like appearance, but with atypical morphologic features (including atypical spindle cells, pleomorphic [multinucleated] cells, pleomorphic lipoblasts and poor circumscription), for which we propose the term "atypical" pleomorphic lipomatous tumor (APLT). Five cases of PLS were also included in this study. We used multiplex ligation-dependent probe amplification to evaluate genetic changes of 13q14. In addition, array-based comparative genomic hybridization was performed on 4 APLTs and all PLSs. Multiplex ligation-dependent probe amplification showed consistent loss of RB1 and its flanking gene RCBTB2 in all cases of APLT. This genetic alteration was also present in all PLSs, suggesting genetic overlap, in addition to morphologic overlap, with APLTs. However, array-based comparative genomic hybridization demonstrated more complex genetic alterations with more losses and gains in PLSs compared with APLTs. APLTs arose in the subcutis (67%) more frequently than in the deep (subfascial) soft tissues (33%). With a median follow-up of 42 months, recurrences were documented in 2 of 12 APLTs for which a long follow-up was available. Herein, we also demonstrate that APLTs share obvious overlapping morphologic, immunohistochemical, genetic and clinical characteristics with the recently defined ASLT, suggesting that they are related lesions that form a spectrum (atypical spindle cell/pleomorphic lipomatous tumor).